High validity of mother-reported use of anti-asthmatics among children: a comparison with a population-based prescription database - Furu, Kari (2011)
OBJECTIVES: To examine the validity of: 1) maternal questionnaire report of children's use of anti-asthmatics using a prescription database as the reference standard, 2) dispensed anti-asthmatics as a measure of asthma using maternal report of children's asthma as the reference standard. STUDY DESIGN AND SETTING: 3394 children in the Norwegian Mother and Child Cohort Study (MoBa) aged seven were linked to the Norwegian Prescription Database (NorPD). Maternal report of both children's use of anti-asthmatics during the preceding year and of the presence of asthma was compared with data on dispensed anti-asthmatics. RESULTS: 2056 mothers responded and reported use of anti-asthmatics the previous year in 125 of 147 children who had been dispensed anti-asthmatics (sensitivity 85.0%). Of 1909 children with no dispensed anti-asthmatics, 1848 had no maternal report of anti-asthmatic use (specificity 96.8%). Mothers reported current asthma in 133 (6.5% of 2056) children, including 122 (5.9%) reported as verified by a doctor. Of these 122, 98 had been dispensed anti-asthmatics during the preceding year (sensitivity 80.3%). Only 1.2% of the children without reported asthma were dispensed anti-asthmatics. CONCLUSION: Mother-reported use of anti-asthmatics during the previous year among 7 year old children is highly valid. Dispensed anti-asthmatics would be a useful proxy for the presence of current asthma when disease data are not available.